Subnational Budget Process and Practices in Nepal : Findings and Observations from an Assessment in Three Pilot Districts - World Bank (Washington, DC, 2014)
Nepal embarked on a process of decentralization, first through the 1999 Local Self Governance Act, which introduced major policy reforms to devolve decision-making power to local bodies, and later through its 2007 interim constitution, which abol¬ished a feudal state structure and established a federal system of governance that prioritized local government. These reforms presented an important opportunity to not only improve efficiency but also engage citizens at the subnational level. However, they have not yet translated into a more efficient use of budget resources at the subnational level or enhanced citizen under¬standing of budget processes. It was in this context that the Budget Transparency Initiative (BTI) piloted an innovative approach in 2011 to simplify, analyze, and disclose budgets at the subnational level and to build awareness and capacity among government officials and citizens that could promote a public dialogue around public expenditures through social accountability approaches. In this context, under the aegis of the BTI, a study was conducted in 2011 to assess the gaps between policies and actual implementation of the budget at the subnational level in three pilot districts in Nepal Kaski, Dolakha, and Nawalparasi. nalysis from the study, in-depth interviews, and focus group discussions revealed several gaps between policy and prac¬tice in subnational budget formulation and execution processes, such as the predominance of top-down processes, lack of cost-benefit analyses in budget allocation decisions, delays in communication of budget ceilings and release of allocations, and capture of user committees. This note describes the institutional framework underlying this context, outlines the methodology used, and presents key findings and observations from the study.